การพัฒนาแบบวัดจิตสาธารณะสำหรับนักศึกษาปริญญาบัณฑิต - สายถวิล แซ่ฮ่ำ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
The objectives of this research were to 1) develop and validate a public mind scale for undergraduate students, 2) compare public mind among undergraduate students with different backgrounds in terms of gender, age, year, home of origin, field of study, monthly income and club, 3) develop the public mind scale criteria for undergraduate students. The sample consisted of 900 undergraduate students. The data analysis was conducted by using the descriptive statistics and inferential statistics including frequency, percentage, means, standard deviation (S.D.), coefficient of variation (C.V.), skewness, kurtosis, Pearson’s correlation, t-test, one-way ANOVA , and second-order confirmatory factor analysis. The research findings were as follow: 1. The public mind scale was the situation test with indicators comprising 4 factors: participate in public, public responsibility, public respect, and public attendance. The public mind scale had content validity (IOC = 0.60 – 1.00) and acceptable discrimination indexes (0.33-0.55). The overall reliability was 0.92. The reliability coefficients of the four subscales were 0.76, 0.76, 0.78 and 0.79, respectively. The result from confirmatory factor analysis suggested that all models fit empirical well (chi-square= 65.86, df = 54, p = 0.13, GFI = 0.99, AGFI = 0.98, RMR = 0.01, RMSEA = 0.02). 2. The comparisons of public mind for among undergraduate students were that female has higher public mind than male, students with age of 20, 22 and 23 years old had higher public mind than those with 21 years old. 2nd and 5th year students had higher public mind than 4th year students. Student from Science, Humanities and Social Sciences fields had higher public mind than Health science. Students attending arts and music club had higher public mind than those attending academic club and those who are not members of any clubs. Students with income lower 15,000 Baht has higher public mind than those having income upper 15,000 Baht. Furthermore, the home of origin of undergraduate students did not impact their public mind. 3. The criteria of public mind scale for undergraduate students were developed using the normalized T-score. The participation in public subscale had raw score between 15-49 (T17.39-T82.61), the public responsibility subscale had raw score between 16-36 (T21.55 -T66.72), public respect subscale had raw score between 19-48 (T17.39 - T68.81), and public attendance subscale had raw score between 17-40 (T20.65 - T67.13).